Beitrag zur Kenntnis der Mikrolepidopterenfauna der Balkanhalbinsel (Epermeniidae, Acrolepiidae, Douglasiidae). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1975)
A survey is made of the new finds that have become known since the publication of our first papers on the Epermeniidae and Acrolepiidae of the Balkan peninsula (Gaedike, 1966a, 1969). A first synopsis is given of the finds of Douglasiidae. Roumania is included in the study. So far, 15 Epermeniiden, 13 Acrolepiidae and 6 Douglasiidae have been identified on the territory under consideration.